Critical thinking in STEM (science, technology, engineering, and mathematics) - ROGOVAYA, O.; LARCHENKOVA, L.; GAVRONSKAYA, Y. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThe purpose of this study is to determine the place of critical thinking in the training of future teachers. To conduct the study, a survey of 200 full-time bachelor students of the Herzen State Pedagogical University of Russia was organized. All students study in Natural Sciences. The study analyzed several integrated tasks that can be aimed at the development of critical thinking. According to the results, critical thinking plays an important role in the educational process, which must be taken into account in the training of future teachers.RESUMENEl propósito de este estudio es determinar el lugar del pensamiento crítico en la formación de futuros maestros. Para llevar a cabo el estudio, se organizó una encuesta a 200 estudiantes de licenciatura a tiempo completo de la Universidad Pedagógica Estatal Herzen de Rusia. Todos los estudiantes estudian en ciencias naturales. El estudio analizó varias tareas integradas que pueden estar dirigidas al desarrollo del pensamiento crítico. Según los resultados, el pensamiento crítico juega un papel importante en el proceso educativo, que debe tenerse en cuenta en la formación de futuros docentes.